التوجه بالسوق وأثره على تعظيم القدرة التنافسية دراسة ميدانية على المنظمات الصناعية الحاصلة على الأيزو في اللاذقية - ميا علي; شيخ ديب صلاح; دغمان لبنى (Latakia University Journal - Economic and Legal Sciences Series, 2013)
تهدف هذه الدراسة إلى التّأكّد من مستوى تطبيق التوجه بالسوق بأبعاده الثلاثة (التوجه بالعميل, التوجه بالمنافسين, والتوجه بالتنسيق الوظيفيّ الداخليّ), والتعرّف إلى أثر هذا التطبيق في القدرة التنافسية للمنظمات الصناعية في اللاذقية والحاصلة على الأيزو, بالإضافة على قياس مستوى ثقافة التوجه بالسوق في المنظمات المذكورة, وتكتسب هذه الدراسة أهميتها بشكلٍ أساسيّ من كون بيئة الدراسة, وعينة الدراسة جديدة بالنسبة لتطبيق التوجه بالسوق في المنظمات الصناعية, كما يعدّ التوجه بالسوق من الأساليب الإدارية الحديثة المطبقة في الكثير من المنظمات الصناعية الناجحة في عالم الأعمال اليوم, الذي يتصف بالتغيرات المتسارعة, والمنافسة الشديدة في السوق, وقد توصلت الدراسة إلى أنّ المنظمات الصناعية التي تضمنها مجتمع البحث تطبق التوجه بالسوق بدرجة عالية, وأنّ هذا التطبيق يؤثر على قدرتها التنافسية, كما أنّ الثقافة التنظيمية اللازمة للتوجه بالسوق موجودة بنسبة مقبولة, وقد أوصت الدراسة بضرورة متابعة الشركات للدّراسات التي تتناول مفهوم التوجه بالسوق، وكيفية تطبيقه وفوائده، حتّى تكون قادرةً على المنافسة في السّوق المحلية والعالمية. This study aims to ascertain the level of application-oriented market dimensions of the three (customer orientation, competitors orientation, and Internal Functional Orientation), and identify the impact of this application on the competitiveness of organizations in Lattakia and developments on the ISO, in addition to measuring the level of a culture oriented to the market in mentioned organizations, and This study is important mainly from the fact that the study environment, and a sample study new to the application-oriented market in industrial organizations, as is the trend in the market of modern management techniques applied in many industry organizations successful in today’s business world, which is characterized by changes rapidly, and intense competition in the market, The study found that industrial organizations included in the research community applied to go the market with a high degree, and that this application affect its competitiveness, and organizational culture necessary to go in the market place and by acceptable, The study recommended the need for follow-up to companies to studies dealing with the concept of market orientation and how to apply and benefits in order to be able to compete in domestic and global market.